Social media and COVID-19 vaccination hesitancy: mediating role of the COVID-19 vaccine perception - Duy Van Nguyen; Phi-Hung Nguyen (Heliyon, 2022)
Individuals' COVID-19 vaccination behaviors were examined when the government introduced a new vaccine into the immunization program. The purpose of this study is to thoroughly examine the effects of COVID-19 risk perception (CR), COVID-19 vaccination perception (VC), and Social Media (SO) on COVID-19 vaccine hesitancy (HE) in Vietnam. Three hundred fifty samples were collected regarding a reluctance to vaccinate against COVID-19 from 6/2021 to 7/2021. This is when immunizations are administered and injected in Vietnam; hence, hesitation regarding injection is rather prevalent. Multivariate regression analysis is conducted on a dataset of 350 Vietnamese respondents using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach. The main results indicated that the Perception Vaccine functions as a link between VC and HE. CR has a positive effect on both HE and VC; whereas VC has a negative impact on HE. Simultaneously, the study illustrates the detrimental effect of SO on immunity by comparing it to the influence of social media. The study's findings also demonstrated the critical role of protection motivational theory (PMT) and information theory in promoting vaccination efforts in Vietnam.